Despite raps, piston sets another jeepney strike - Yee, Jovic (2017)
The planned "transport holiday" will be Piston's third this year and is set two weeks after another group held a strike over the same issue.
Keywords: Pagkakaisa ng mga Samahan ng mga Tsuper at Operator Nationwide -- Protests, demonstration, etc